CEMARAN ASPERGILLUS FLAVUS PENGHASIL AFLATOKSIN B1 PADA JAGUNG MANIS(ZEA MAYS SACCHARATA) SELAMA PENYIMPANAN - Dewi Aristyawati, Ni Putu; Indri Hapsari A., Ni Made; Selamet Duniaji, Agus (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
Corn is one of the commodities that have high contamination of molds specifically A.flavus. This study aims to determine the contamination of A.flavus in sweet corn during storage, to determine the population of A.flavus that contaminate sweet corn during storage, and to find out if A.flavus that contaminates sweet corn during storage can produce aflatoxin B1. This research uses experimental method. Corn samples were stored at room temperature (300C ± 10C) and low temperature (70C ± 10C) wrapped with PE plastic stored from day 0 to day 6. The results of this study indicate that sweet corn stored at room temperature was contaminated with yeast mold on day 0 5,2 x 108 CFU/g and day 6 2,5 x 108 CFU/g and sweet corn stored at low temperature was contaminated on day 0 4,0 x 107 CFU/g and day 6 4,0 x 108 CFU/g. Sweet corn stored at room temperature contaminated with mold on day 0 1,0 x 106 CFU/g and day 6 is 3,5 x 106 CFU/g and sweet corn stored at low temperature was contaminated on 0 1,0 x 106 CFU/g and day 6 4,0 x 106 CFU/g. The sweet corn that was stored at low temperature was contaminated by A.flavus on day 3 1,2 x 106 CFU/g and day 6 <1.0 x 106 CFU / g and at low temperature was contaminated on day 2 1,0 x 106 CFU/g and day 6 1.0 x 106 CFU/g. Aflatoxin B1 day 0 at room temperature was 29.40 ppb and on day 6 29.08 ppb. Aflatoksin B1 day 0 at low temperature was 30.03 ppb and on day 6 was 29.97 ppb.